The Role of Political Elites in the Development of New Villages in Malaysia - Wee, Jeck Seng; Phang, Siew Nooi; Khalil, Samihah (Macrothink Institute, 2018)
Political elites comprise a small group that has power and influence over the “others” in society.Basically, political elites play an important role in the decision-making process of the community.New Villages in Malaysia are influenced by political elites who are the representatives of the village community. These political elites are members of the Malaysian Chinese Association (MCA), a coalition party of the ruling political party.MCA's political elite play an important role in safeguarding the welfare and affairs of the New Village residents. New Villages refer to a Chinese New Village which is a re-settlement site set up during the Communist emergency period of British rule in Malaysia in the mid-1950s.The role of the MCA's political elite has helped to create the New Village Master Plan 2005 which serves as a guide and reference to the Federal Government and the State Government in the development of New Villages.However, limited provisions and unclear policies have resulted in New Villages facing a multitude of problems and have frustrated development in New Villages especially in tandem with the requirements of national development.The residents of New Villages are neglected, and many are experiencing social and economic problems.The paper evaluates these problems with reference to the role of local leaders and development objectives for New Villages in the context of national goals.